2009
DOI: 10.1152/japplphysiol.00049.2008
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of coronary flow reserve in aortic stenosis

Abstract: Coronary flow reserve (CFR) is markedly reduced in patients with severe aortic valve stenosis (AS), but the exact mechanisms underlying this impairment of CFR in AS remain unclear. Reduced CFR is the key mechanism leading to myocardial ischemia symptoms and adverse outcomes in AS patients. The objective of this study was to develop an explicit mathematical model formulated with a limited number of parameters that describes the effect of AS on left coronary inflow patterns and CFR. We combined the mathematical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 50 publications
5
56
0
5
Order By: Relevance
“…Accordingly, Garcia et al [31] have reported that when the aortic valve indexed EOA is larger than 0.8 to 0.9 cm 2 /m 2 , there is no significant impact on CFR which decreases sharply when the indexed EOA is lower than this threshold and becomes almost completely exhausted when the indexed EOA is below 0.5 cm 2 /m 2 .…”
Section: Coronary Flow Reservementioning
confidence: 99%
“…Accordingly, Garcia et al [31] have reported that when the aortic valve indexed EOA is larger than 0.8 to 0.9 cm 2 /m 2 , there is no significant impact on CFR which decreases sharply when the indexed EOA is lower than this threshold and becomes almost completely exhausted when the indexed EOA is below 0.5 cm 2 /m 2 .…”
Section: Coronary Flow Reservementioning
confidence: 99%
“…21, 22 Furthermore, longitudinal function is governed by the subendocardial myocardial fibers, which are aligned longitudinally and more sensitive to microvascular ischemia. 12, 23 The selective impairment in longitudinal function in patients with AS is thus related to the increase in subendocardial stress and associated reduction in coronary flow reserve. Consequently, the improvement in coronary flow reserve after AVR, secondary to an increase in the effective orifice area, results in a more efficient myocardial arterial supply and improved longitudinal function.…”
Section: Longitudinal Myocardial Dysfunction In Patients With Asmentioning
confidence: 99%
“…It is known that angina pectoris, myocardial ischaemia, inadequate left ventricular hypertrophy, smaller coronary artery dimensions and reduced coronary flow reserve occur in most of AS patients (5,(10)(11)(12)(13)(14)(15)(16). The reduction of coronary flow reserve that is associated with AS can be explained by the concomitant presence of reduced myocardial supply as a result of decreased coronary perfusion pressure, and increased myocardial metabolic demand as a result of increased left ventricular workload (16).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of coronary flow reserve that is associated with AS can be explained by the concomitant presence of reduced myocardial supply as a result of decreased coronary perfusion pressure, and increased myocardial metabolic demand as a result of increased left ventricular workload (16). CFR was found to be similarly decreased in AS patients with and without severe left anterior descending coronary artery (LAD) disease (17).…”
Section: Discussionmentioning
confidence: 99%